Distributed transit compartments for arbitrary lifespan distributions in aging populations. (7th September 2015) - Koch, Gilbert; Schropp, Johannes
Abstract: Transit compartment models (TCM) are often used to describe aging populations where every individual has its own lifespan. However, in the TCM approach these lifespans are gamma-distributed which is a serious limitation because often the Weibull or more complex distributions are realistic. Therefore, we extend the TCM concept to approximately describe any lifespan distribution and call this generalized concept distributed transit compartment models (DTCMs). The validity of DTCMs is obtained by convergence investigations. From the mechanistic perspective the transit rates are directly controlled by the lifespan distribution. Further, DTCMs could be used to approximate the convolution of a signal with a probability density function. As example a stimulatory effect of a drug in an aging population with a Weibull-distributed lifespan is presented where distribution and model parameters are estimated based on simulated data. Abstract : Highlights: We extend the transit compartment concept to approximately describe any lifespan distribution in aging populations. The developed distributed transit compartments are applied to solve the convolution integral in distributed lifespan models. The distributed transit compartments could be similarly implemented as traditional transit compartments. Applications to typical pharmacokinetics/pharmacodynamics questions are provided.